Mediating Social Challenges: Art, Storytelling, and Critical Pedagogies (transcript Verlag, 2025)
In the face of social inequalities, digital divides, hegemonic power relations, capitalist conflicts of interests, asymmetric gender relations and international border and migration regimes, educational and social actions are becoming more challenging. Mediating these social challenges demands new methods and approaches. Thus, the contributors to this volume use critical pedagogies to reflect on art, literature, storytelling, and digital methods as a means to mediating social challenges in teaching practices. The contributions challenge normative perceptions of identity while also promoting students' multiliteracy skills.